How important are today's teacher development program contents for primary school teacher? - Jayanti, Jayanti; Wahyudin, Dinn (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
Teacher development program (TDP) will only be effective when it answers the teacher's need. This study aims to find out how important the training content that has been delivered in the TDP. The training contents listed in this study drawn from the Teacher Working Group, the School of Master Teacher program organized by Sekolah Guru Indonesia Dompet Dhuafa and teacher development at Sukma Bangsa School. A total of 327 primary school teachers have participated in the study which was designed based on survey model. The study was limited to primary school teachers due to different teacher needs of other school levels may be occurred. The data of this study were obtained by using a questionnaire comprised of 13 close-ended items in the form of the rating scale. Descriptive statistics include the percentage, frequency, mean, and standard deviation for data analysis. According to the study results, 84,1% of respondents chosen classroom management as the most important training content to learn. Another indication of the result is that the teachers also need to learn teaching and learning models, developmental psychology, teaching motivation, teaching and learning evaluation, teaching and learning media, technology-based learning, lesson plan, 2013 curriculum, classroom display, public speaking and literacy-based learning that more than 50% teachers defined them as very important to learn. However, only 47% of respondents mentioned Classroom Action Research is very important to learn. Based on the results of this study, the designer of TDP suggested considering classroom management as the first priority to deliver in the TDP followed by teaching and learning models, developmental psychology, teaching motivation, teaching and learning evaluation, teaching and learning media, technology-based learning, lesson plan, 2013 curriculum, classroom display, public speaking and literacy-based learning. In addition, it has to pay more attention to the teacher's need level of Classroom Action Research that is still very low due to improving their motivation to do research. Seberapa pentingkah muatan program pengembangan guru saat ini bagi guru sekolah dasar?Program pengembangan guru dinilai efektif jika muatan materi yang diberikan sesuai dengan kebutuhan guru. Penelitian ini bertujuan untuk mengetahui seberapa penting muatan pelatihan yang selama ini dibawakan dalam program pengembangan guru. Muatan pelatihan yang dimasukkan ke dalam daftar muatan pelatihan pada penelitian ini diambil dari Kelompok Kerja Guru (KKG), program School of Master Teacher yang diselenggarakan oleh Sekolah Guru Indonesia Dompet Dhuafa dan program pengembangan guru di Sekolah Sukma Bangsa. Sebanyak 327 guru sekolah dasar telah berpartisipasi dalam studi yang dirancang berdasarkan model survei. Penelitian ini terbatas pada guru sekolah dasar sebab kebutuhan guru pada jenjang pendidikan lainnya dapat berbeda. Data penelitian ini diperoleh dengan menggunakan kuesioner yang terdiri dari 13 soal tertutup dalam bentuk skala penilaian. Statistik deskriptif termasuk persentase, frekuensi, mean, dan deviasi standar dihitung untuk analisis data. Studi ini menunjukkan bahwa manajemen kelas adalah konten pelatihan yang paling penting untuk dipelajari oleh guru sekolah dasar dimana sebanyak 84,1% responden memilihnya sebagai muatan yang sangat penting dipelajari. Indikasi lain dari hasil penelitian ini adalah bahwa para guru juga perlu belajar model-model pembelajaran, psikologi perkembangan, motivasi mengajar, evaluasi belajar mengajar, media pembelajaran, pembelajaran berbasis teknologi, rencana pelajaran, kurikulum 2013, display kelas, public speaking dan pembelajaran berbasis literasi dimana lebih dari 50% guru mendefinisikannya sebagai materi yang sangat penting untuk dipelajari. Sebaliknya penelitian tindakan kelas masih dianggap belum begitu penting dimana hanya 47, 1% yang menilainya sangat penting untuk dipelajari. Berdasarkan hasil studi ini, perancang program pengembangan guru pada masa mendatang disarankan agar memprioritaskan manajemen kelas untuk disampaikan dalam program pengembangan guru, diikuti oleh model-model pembelajaran, psikologi perkembangan, motivasi mengajar, evaluasi belajar mengajar, media pembelajaran, pembelajaran berbasis teknologi, rencana pelajaran, kurikulum 2013, display kelas, public speaking dan pembelajaran berbasis literasi. Namun dengan melihat tingkat kebutuhan guru yang masih rendah terhadap penelitian tindakan kelas perlu menjadi perhatian agar minat guru untuk melakukan penelitian dapat ditingkatkan.